Tropical agriculture : Selected handbooks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'Tropical agriculture: Selected handbooks', 1989, 119pp. ISBN 90 6832 627 9